Knowledge, Attitude, and Practice towards Hepatitis B Virus Among Pregnant Women Attending Antenatal Care at the Public Hospitals of Afar Regional State, Ethiopia - Edris, Hussen; SREEMANARAYANA , V. (YCAB Publisher, 2025)
Background:Hepatitis B virus (HBV) poses a significant global public health challenge, particularly in highly endemic regions such as Ethiopia, where mother-to-child transmission remains a major concern. Despite the critical importance of this issue, limited research has been conducted on the knowledge, attitudes, and practices (KAP) of pregnant women regarding HBV infection. This study aims to assess the knowledge, attitudes, and practices of pregnant women attending antenatal care in public hospitals in the Afar region, Ethiopia, concerning HBV infection. Method:A cross-sectional study was conducted in five public hospitals in the Afar region, Eastern Ethiopia, from August 2023 to April 2024. The study targeted 442 pregnant women receiving antenatal care at these facilities. Data were collected through face-to-face interviews using a pretested, structured questionnaire and analyzed using SPSS software. Associations between variables were examined through bivariate and multivariable logistic regression analyses, with a p-value of less than 0.05 considered statistically significant. Results:Among the 442 participants, 10.4% (95% CI: 7.7–13.6), 19.2% (95% CI: 15.7–23.2), and 17% (95% CI: 13.6–20.8) demonstrated good knowledge, positive attitudes, and good practices regarding HBV, respectively. Higher educational attainment (AOR = 10.83, 95% CI: 3.97–29.6) was significantly associated with better knowledge, attitudes, and practices. Urban residence (AOR = 2.04, 95% CI: 1.02–4.08) was linked to good knowledge and positive attitudes, while higher income (AOR = 5.16, 95% CI: 1.49–17.9) was strongly associated with good knowledge. Conversely, a smaller family size (AOR = 0.428, 95% CI: 0.195–0.942) was associated with poorer practices. Conclusion:Pregnant women in the Afar region exhibit low levels of knowledge, poor practices, and negative attitudes toward HBV infection. To address these gaps, the implementation of comprehensive HBV screening programs and targeted health education campaigns is crucial to enhance awareness and improve preventive behaviors among this population. Keywords:knowledge; attitudes; practices; pregnant women; Hepatitis B virus; Afar Eastern Ethiopia